Reflections of a Textbook Author - Mankiw, N. Gregory (Journal of Economic Literature, 2020)
In this essay, I reflect on textbook writing after three decades of participating in the activity. I address the following questions: What perspective should textbooks take? What is the best approach to teaching microeconomics? What is the best approach to teaching macroeconomics? How does the content of the introductory course evolve? How much material should textbooks include? Are textbooks too expensive? How is digital technology changing the market for textbooks? Who should become a textbook author? ( JEL A22)